Genomic Diversity of CRESS DNA Viruses in the Eukaryotic Virome of Swine Feces - Enikő Fehér; Eszter Mihalov-Kovács; Eszter Kaszab; Yashpal S. Malik; Szilvia Marton; Krisztián Bányai (Microorganisms, 2021)
Replication-associated protein (Rep)-encoding single-stranded DNA (CRESS DNA) viruses are a diverse group of viruses, and their persistence in the environment has been studied for over a decade. However, the persistence of CRESS DNA viruses in herds of domestic animals has, in some cases, serious economic consequence. In this study, we describe the diversity of CRESS DNA viruses identified during the metagenomics analysis of fecal samples collected from a single swine herd with apparently healthy animals. A total of nine genome sequences were assembled and classified into two different groups (CRESSV1 and CRESSV2) of the Cirlivirales order (Cressdnaviricota phylum). The novel CRESS DNA viral sequences shared 85.8–96.8% and 38.1–94.3% amino acid sequence identities for the Rep and putative capsid protein sequences compared to their respective counterparts with extant GenBank record. Data presented here show evidence for simultaneous infection of swine herds with multiple novel CRESS DNA viruses, including po-circo-like viruses and fur seal feces-associated circular DNA viruses. Given that viral genomes with similar sequence and structure have been detected in swine fecal viromes from independent studies, investigation of the association between presence of CRESS DNA viruses and swine health conditions seems to be justified.